Linguistics of Speech, Complexity and the role of African French in General Linguistics - (:unkn) unknown (My University, 2019)
The transformation of the object French in Africa over the last 50 years goes hand in hand with the transformation of sociolinguistics in the broadest sense. Studies initially focused on mother tongue interference with French among African speakers, based on “on-the-fly” surveys; more recently, they have concentrated on language-related social practices particularly in urban areas. We will argue that French in Africa is an opportunity for research on spoken French, and for the study of language in interaction in general. The major challenge of its constitution as an object of future linguistic study will be to develop a methodology inspired by corpus linguistics and concerned with the intrinsic characteristics of the data. The most original instances among these data are oral, e.g. related to time and the discursive elaboration activity of the speaker.
Keywords: African Research